PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA DI PROVINSI RIAU BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Rai Iqsandri (Ensiklopedia Social Review, 2019)
Narcotics are substances or drugs that come from plants or not plants, both synthetic and semisynthetic, which can cause a decrease or change of consciousness, loss of taste, reduce to eliminate pain, and can cause dependence. This study aims to explain the law enforcement against narcotics misuse in Riau Province based on Law Number 35 of 2009 concerning Narcotics. The method used in this research is sociological legal research. The results of this study explain that narcotics abuse can be categorized as a criminal offense as regulated in Act Number 35 of 2009 concerning Narcotics. Riau Province is one of the main routes, especially sea lane, narcotics distribution from abroad to Indonesia. The types of narcotics that are most widely circulated and abused in Riau Province are marijuana and methamphetamine. In order to eradicate criminal acts of narcotics abuse in Riau Province which are already very alarming, strict law enforcement is needed along with the application of sanctions that can provide a deterrent effect, namely the application of the death penalty to narcotics abuse offenders.